Complete genome sequence of mitochondrial DNA (mtDNA) of Chlorella sorokiniana. (3rd March 2016) - Orsini, Massimiliano; Costelli, Cristina; Malavasi, Veronica; Cusano, Roberto; Concas, Alessandro; Angius, Andrea; Cao, Giacomo
Abstract: The complete sequence of mitochondrial genome of the Chlorella sorokiniana strain (SAG 111-8 k) is presented in this work. Within the Chlorella genus, it represents the second species with a complete sequenced and annotated mitochondrial genome (GenBank accession no. KM241869). The genome consists of circular chromosomes of 52, 528 bp and encodes a total of 31 protein coding genes, 3 rRNAs and 26 tRNAs. The overall AT contents of the C. sorokiniana mtDNA is 70.89%, while the coding sequence is of 97.4%.